Efecto de las condiciones de cultivo sobre parametros del modo de accion de Metarhizium anisopliae - Villamizar R, L.F.=700 1 Cotes, A.M.
(Es, En)
Ilus., 12 ref.
Keywords: METARHIZIUM ANISOPLIAE; HONGOS ENTOMOPATOGENOS; VIRULENCIA; GERMINACION; CONIDIA; COLOMBIA